DESKRIPSI KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN MOTIVASI BELAJAR SISWA SMP NEGERI 1 SUMBANG - Akhsani, Lukmanul; Rahayu, Puji (AlphaMath : Journal of Mathematics Education, 2018)
This research aimed to describe students’ mathematical creative thinking ability at SMP Negeri 1 Sumbang. This research belongs to descriptive qualitative research. The subjects of this research were the students Grade VII G of SMP Negeri 1 Sumbang. The samples were taken using purposive sampling technique. The data were collected using questionnaire, test, interview, and documentation. The data validity test used in this research was triangulation. The results of this research illustrate that: 1) Low category students could meet one indicator of mathematic creative thinking ability i.e. fluency. Their learning motivation was good. They preferred to learn in a group. They were enthusiastic when they were given awards during the instruction. 2) Medium category students could meet two indicators of mathematic creative thinking ability i.e. fluency and flexibility. Their learning motivation was very good. They were active during the instruction and they preferred to work autonomously. They sometimes reviewed the lesson that had been learned at school. 3) High category students could master mathematic creative thinking ability i.e. fluency and flexibility. Their learning motivation was very good. When they met hard questions, they would try to solve the problems well. During the instruction, they were active and they preferred to work autonomously. KEY WORDS: Mathematical Creative Thinking, Learning Motivation